2017
DOI: 10.1007/s10068-017-0198-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of slightly acidic electrolyzed water ice and grapefruit seed extract ice on shelf life of brown sole (Pleuronectes herzensteini)

Abstract: The effects of slightly acidic electrolyzed water ice (SAEW-ice) and grapefruit seed extract ice (GSE-ice) on changes in brown sole quality during storage were determined using microbial, chemical, and sensory analyses to prolong the shelf life of brown sole. Microbiological analyses showed that GSE-ice storage was more effective for inhibiting the growth of total plate count, , and HS-producing bacteria than SAEW-ice storage. Chemical indexes of brown sole showed that SAEW-ice and GSE-ice storage extended the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Ovissipour et al () reported that the WAEW at available chlorine concentrations (ACC) of 10 mg/ml, pH 3.55, and oxidation–reduction potentials (ORP) of 950 mV could significantly inhibit the growth of Vibrio parahaemolyticus , Listeria monocytogenes , Aeromonas hydrophila , and Campylobacter jejuni . In addition, Jung, Ko, Jang, Park, and Oh () further indicated that WAEW significantly inhibited the growth of TVC, Pseudomonas , and H 2 S‐producing bacteria on Pleuronectes herzensteini stored at 0–1°C for 30 days. Besides, Xuan et al () showed that WAEW could inhibit the increase of peroxide value, total volatile basic nitrogen (TVB‐N), and thiobarbituric acid reactive substance (TBARS) contents and thus concluded that WAEW had potential to be applied for maintaining the freshness of fish during cold storage.…”
Section: Introductionmentioning
confidence: 97%
“…Ovissipour et al () reported that the WAEW at available chlorine concentrations (ACC) of 10 mg/ml, pH 3.55, and oxidation–reduction potentials (ORP) of 950 mV could significantly inhibit the growth of Vibrio parahaemolyticus , Listeria monocytogenes , Aeromonas hydrophila , and Campylobacter jejuni . In addition, Jung, Ko, Jang, Park, and Oh () further indicated that WAEW significantly inhibited the growth of TVC, Pseudomonas , and H 2 S‐producing bacteria on Pleuronectes herzensteini stored at 0–1°C for 30 days. Besides, Xuan et al () showed that WAEW could inhibit the increase of peroxide value, total volatile basic nitrogen (TVB‐N), and thiobarbituric acid reactive substance (TBARS) contents and thus concluded that WAEW had potential to be applied for maintaining the freshness of fish during cold storage.…”
Section: Introductionmentioning
confidence: 97%
“…WAEW and daphnetin treatments could effectively reduce the degradation of ATP, which can be attributed to the inhibitory effect of WAEW and daphnetin on nucleotide-degrading enzymes and bacteria responsible for nucleotide degradation (44). As reported by Jung et al (45), the brown sole (Pleuronectes herzensteini) treated with WAEW could delay the degradation of nucleic acids-related substances in the muscle and retain the freshness of the fish. According to Alasalvar et al (46), the conversion of ATP to IMP was a totally autolytic process within 1-2-day storage; however, the subsequent breakdown of IMP to Hx was caused by both fish and microbial enzymes.…”
Section: K Value Resultsmentioning
confidence: 83%
“…El porcentaje de efectividad de cada tratamiento con respecto al control se calculó con la siguiente fórmula. Las semillas cítricas y los ácidos ascórbico y láctico tienen efectos antimicrobianos (Tajkarimi y Ibrahim, 2011;Damián-Reyna et al, 2017;Jung et al, 2017). De acuerdo con la información proporcionada por el fabricante, el producto ECD contiene un extracto estandarizado de semilla de cítricos y glicerina; de manera general, entre los componentes encontrados en las semillas cítricas están los ácidos (2E)-hidroxicinámico, gálico, siríngico y rosmarínico entre otros (Moulehi et al, 2012), cuya forma no ionizada predomina a pH ácido, atraviesan la membrana celular hasta llegar al citoplasma.…”
Section: Resultados Y Discusiónunclassified